Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.